2017
DOI: 10.3233/nib-170121
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid and Serum Markers of Inflammation in Patients with Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) is the most common inflammatory demyelinating disease of the central nervous system. Cytokines plays critical role in pathogenesis of disease. Until now, serum and Cerebrospinal fluid (CSF) levels of many biomarkers and their correlations with MS features have been evaluated. In this study, we measured serum and CSF levels of C-reactive protein (CRP) and IFN-␥ in patients with Multiple sclerosis and their correlations with paraclinical features of MS have been evaluated. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Nazeri et al in a case control study showed that the serum levels of high-sensitivity C-reactive protein (hs-CRP) was higher in patients with MS specially patients with cerebellar and brain stem symptoms (Nazeri et al, 2021). Also, Farrokhi M and Polachini in other studies found a significant increase in the serum levels of inflammatory markers, Like CRP in MS patients compared to the control group (Polachini et al, 2014;Farrokhi et al, 2017). However, Yoon et al reported that CRP may be a useful marker for the detection of inflammationmediated MS relapses (Yoon et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Nazeri et al in a case control study showed that the serum levels of high-sensitivity C-reactive protein (hs-CRP) was higher in patients with MS specially patients with cerebellar and brain stem symptoms (Nazeri et al, 2021). Also, Farrokhi M and Polachini in other studies found a significant increase in the serum levels of inflammatory markers, Like CRP in MS patients compared to the control group (Polachini et al, 2014;Farrokhi et al, 2017). However, Yoon et al reported that CRP may be a useful marker for the detection of inflammationmediated MS relapses (Yoon et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…The patient infected with serotype 15B was also living with HIV and the patient with serotype 14 was neither HIV nor tuberculosis positive (Supplementary Table 1). All patients had inflammatory cytokine concentrations which were markedly higher than those reported in the literature as normal values in CSF (IL-6: 0 -5 pg/ml; IL-8: 10 -15 pg/ml; TNFa: 0 -5 pg/ ml; IL-10: 0 -29 pg/ml; IFN-g: 0 -37 pg/ml; IL-1b: 0 -4 pg/ml) (Kothur et al, 2016;Farrokhi et al, 2017;Liu et al, 2020) shown in Supplementary Figure S3. We did not perform statistical analysis on the values because there was one patient per serotype and because the patients may have been at different stages of disease.…”
Section: Fatal Outcome For Patients Infected With Strains Of Serotype...mentioning
confidence: 74%
“…One potential therapeutic mechanism of CoQ 10 is its ability to adjust the immune response [49]. Inflammation is a key contributor to axonal injury in MS, of which anti-inflammatory cytokines are decreased and pro-inflammatory cytokines are increased in the CSF [50,51]. A study by Sanoobar et al [7] reported that CoQ 10 supplementation for 12 weeks (500 mg/ day) did not alter levels of anti-inflammatory cytokines transforming growth factor-β (TGF-β) and interleukin (IL)-4 in the serum of MS patients compared to the placebo group.…”
Section: Coq 10 Limitations In Msmentioning
confidence: 99%